REFLEXIONS ON MARIANO MELGAR’S POETRY - Martos Carrera, Marco (2011)
This article is about Mariano Melgar’s poetry under the context of the PeruvianIndependence. It refers to two traditions that converge in his fervid inspiration:the oral tradition of Quechua origin, and the written tradition of western roots. Itanalyzes some texts which the Arequipa-born writer managed to sketch out in hisshort life. It is argued that Melgar leads a literary line of profound originality inthe national literature.o